Innovativeness and export competitiveness in the East African Community - Anthony Moni Olyanga; Isaac M. B. Shinyekwa; Muhammed Ngoma; Isaac Nkote Nabeta; Timothy Esemu; Moses Kamya (Modern Supply Chain Research and Applications, 2022)
Purpose The purpose of this paper is to examine the influence of innovation indicators: Internet usage, patent rights, innovation in exporting countries and innovation in the importing country on the export competitiveness of firms in the East African Community (EAC). Design/methodology/approach The study adopted the structural gravity model and the Poisson Pseudo Maximum Likelihood a nonlinear estimation method that was applied in STATA on balanced panel data from 2007 to 2018. Data were obtained from World Bank International Trade Center and World Bank development indicators. Findings Results show that innovation in the importing country, innovation in the exporting country and patent rights of exports are positive and significant predictors of export competitiveness in developing countries. While Internet usage is an insignificant predictor in the EAC. Research limitations/implications There is a need to examine the complicated nature of the EAC economy to further this study's findings. Practical implications Exporting countries need to take deeper reforms as regards structural transformation to enable firms to integrate into the Global Value Chains (GVCs) to enable them to increase their productivity by reviewing the existing policies to match the changes in the market. Originality/value This study explains the complex dynamic interactions of technological innovation indicators in the EAC using quantitative data and that this interaction has an effect on the export competitiveness in import-oriented countries with less harmonization in their trade policies.
Keywords: 650; East African community; Export competitiveness; Innovation in export country; Innovation in import country; Innovation indicators; Internet usage; Patent rights protection